PRINCIPLES OF ORGANIZING BUSINESS GAMES (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2022)
In the article basic principles of organization of business games are examined as one of activemethods of studies. Business games are an active method of studies, most near to the real future professional activityof students. Advantage of business games consists in that, being the model of the real activity, they give anopportunity considerably to shorten an operating cycle and to show the same to the participants simultaneously, towhat end-point will bring their decisions over and actions. Business games are both global(management a company)and local(realization of negotiations, preparation of businessplan, report and others like that). The use of this methodallows to the future specialists to execute different professional functions and due to it to extend own ideas aboutorganization and mutual relations of her employees. Business games are useful enough from the point of view ofmaking of practical, administrative(stowage of plans, realization of conferences, negotiations) and behavior skills (ofsatisfaction of necessities of clients, oriented to quality, collaboration). They are less effective for mastering oftheoretical knowledge and capture new professions. Business games are a cost, as for their preparation needed thespecial providing, special skills and much time enough. Effective is an analysis of business game that has an emergencyvalue for efficiency of this type of studies, also requires participation of the specially prepared instructors.Basic principles of constructing and organization of business games are distinguished: principle of imitationdesign of concrete terms of playing design of maintenance and forms of professional activity; principle of problem ofmaintenance of imitation design and process of his development is in a playing model; principle of joint activity;principle of dialogic commonunication; principle of двоплановості of playing educational activity.